High-precision nano soldering paste and preparation method thereof

Through the raw materials and grinding technology with specific ratios, high-precision nano solder paste is prepared, solving the problems of degradation in performance and short service life of existing solder paste, and achieving higher storage stability, expansion rate and wetting performance.

CN119525815AActive Publication Date: 2025-02-28深圳市华远金属有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411493873.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing high-precision nano solder paste may degrade performance during storage, have short service life and insufficient expansion rate, which will affect the welding effect.

Method used

Specific raw materials and ratios, including solder powder, flux, glucomannan and polyethylene glycol modified aliphatic epoxy resin, are used, with a weight ratio of 85-95:10-15:1-3:1-3, and are made by grinding to an average particle size of 100-250 nm.

Benefits of technology

The storage stability, service life, expansion rate and wetting properties of solder paste are improved, making it more suitable for precision electronic packaging.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of soldering paste. The invention discloses high-precision nano soldering paste and a preparation method thereof. The high-precision nano soldering paste comprises soldering powder, soldering flux, glucomannan and polyethylene glycol modified aliphatic epoxy resin. The scaling powder comprises the following raw materials: an active agent, a surfactant, a thixotropic agent, an antioxidant, a corrosion inhibitor, a film-forming agent and a solvent. The preparation method comprises the following steps: stirring and mixing an active agent and a solvent to prepare a premixed solution; sequentially adding a surfactant, a thixotropic agent, an antioxidant, a film-forming agent and a corrosion inhibitor into the premixed liquid, and stirring and mixing to obtain the soldering flux; soldering powder, soldering flux, glucomannan and polyethylene glycol modified aliphatic epoxy resin are mixed, stirred and ground, and the high-precision nano soldering paste is prepared. The prepared high-precision nano soldering paste is good in storage stability, long in service life, high in expansion rate and good in wettability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solder paste, and in particular to a high-precision nano solder paste and a preparation method thereof. Background Art

[0002] With the rapid development of information technology, electronic products are becoming more powerful and smaller. This trend also drives electronic components to develop in the direction of high density and high precision. At the same time, traditional solder paste can no longer meet the needs of modern electronic assembly, especially in the field of precision electronic packaging.

[0003] Traditional solder pastes are mainly suitable for soldering electronic components with larger spacing. They are usually composed of micron-level solder alloy powder and flux, which are suitable for looser soldering spacing. However, with the miniaturization of electronic products, the assembly density of components on PCB boards is getting higher and higher, and the spacing between pads is getting smaller and smaller, which requires solder paste to have higher precision and reliability.

[0004] In this situation, high-precision nano solder paste came into being. It uses nano-level solder alloy powder, which is much smaller than traditional micron-level solder alloy powder. The emergence of high-precision nano solder paste solves the problems encountered by traditional solder paste in precision electronic assembly, such as insufficient wetting performance and low solder joint reliability. It can meet the needs of high-density packaging and is suitable for high-performance computing chips, fine-pitch components, medical electronic equipment, and aerospace electronics.

[0005] However, the existing high-precision nano solder paste may degrade during storage, affecting its service life. There is also room for further improvement in the expansion rate. If the expansion rate is insufficient, it will limit the wettability and filling ability of the solder paste, affecting the welding effect.

[0006] Therefore, there is an urgent need to develop a high-precision nano solder paste with good storage stability, long service life, high expansion rate and good wetting performance. Summary of the invention

[0007] In order to solve at least one of the above technical problems, a high-precision nano solder paste with good storage stability, long service life, high expansion rate and good wetting performance is developed. The present application provides a high-precision nano solder paste and a preparation method thereof.

[0008] On the one hand, the present application provides a high-precision nano solder paste, comprising solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin, wherein the weight ratio of the solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin is 85-95:10-15:1-3:1-3; The soldering flux comprises, by mass percentage, 6.3% to 10% of active agent, 0.25% to 1.5% of surfactant, 4% to 10% of thixotropic agent, 1% to 5% of antioxidant, 1% to 3% of corrosion inhibitor, 1% to 5% of film former, and the balance is solvent.

[0009] By adopting the above technical scheme, the present application adopts specific raw materials and proportions, and the high-precision nano solder paste prepared has good storage stability, long service life, high expansion rate, and good wetting performance. The present application adds glucomannan, which can improve the stability of high-precision nano solder paste and reduce stratification. The present application also adds polyethylene glycol-modified aliphatic epoxy resin, which can improve the expansion rate of solder paste, improve wettability, prevent solder powder from agglomerating, improve the storage stability of solder paste, and extend service life.

[0010] Optionally, the polyethylene glycol-modified aliphatic epoxy resin is prepared by polyethylene glycol and an aliphatic epoxy resin, and the weight ratio of the polyethylene glycol to the aliphatic epoxy resin is 1:3-5.

[0011] By adopting the above technical solution, the specific weight ratio of polyethylene glycol and aliphatic epoxy resin in the present application can obtain the best performance.

[0012] Optionally, the molecular weight of the aliphatic epoxy resin is 600 to 1000, and the epoxy equivalent of the aliphatic epoxy resin is 100 to 300 g / Eq.

[0013] By adopting the above technical solution, the molecular weight and epoxy equivalent of the aliphatic epoxy resin of the present application can balance the performance of the polyethylene glycol-modified aliphatic epoxy resin, so that the comprehensive performance of the solder paste is better.

[0014] Optionally, the active agent is selected from at least one of maleic acid, p-toluenesulfonic acid and sulfosalicylic acid.

[0015] By adopting the above technical solution, the activator of the present application can improve the activity of solder paste, promote the chemical reaction between solder powder and pad, thereby improving the wetting performance, and can also remove oxides on the surface of the pad to ensure good electrical connection.

[0016] Optionally, the surfactant is selected from at least one of dibromo-butene-diol, cyclohexylamine hydrobromide and 3-bromo-1-propanol.

[0017] By adopting the above technical solution, the surfactant of the present application can reduce the interfacial tension between the solder powder and the pad, thereby improving the wetting properties of the solder paste, and also helping the solder paste to spread better and increase the expansion rate.

[0018] Optionally, the thixotropic agent is selected from at least one of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydrogenated castor oil.

[0019] By adopting the above technical solution, the thixotropic agent of the present application can improve the thixotropy of the solder paste, making it easier to control and prevent excessive flow.

[0020] Optionally, the antioxidant is selected from at least one of N,N'-di-sec-butyl-p-phenylenediamine, mercaptobenzothiazole and triphenyl phosphite.

[0021] By adopting the above technical solution, the antioxidant of the present application can prevent the components in the solder paste from oxidizing, thereby improving the storage stability and service life of the solder paste.

[0022] Optionally, the corrosion inhibitor is selected from at least one of benzotriazole, 2-methylbenzimidazole and triethanolamine; and the film-forming agent is selected from at least one of polyvinyl alcohol, polyvinyl pyrrolidone and methyl hydrogenated rosin.

[0023] By adopting the above technical solution, the corrosion inhibitor of the present application can protect the solder joint from corrosion and improve the long-term reliability of the solder joint. The film-forming agent of the present application can form a protective film around the solder joint to protect the solder joint from oxidation and corrosion.

[0024] Optionally, the solvent is selected from at least one of ethanol, isopropanol and propylene glycol.

[0025] In a second aspect, the present application provides a method for preparing the above-mentioned high-precision nano solder paste, comprising the following steps: S1, stirring and mixing the active agent and the solvent to prepare a premixed solution; S2, adding the surfactant, thixotropic agent, antioxidant, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, mixing and stirring the solder powder, the soldering flux, the glucomannan and the polyethylene glycol-modified aliphatic epoxy resin, and grinding them to an average particle size of 100 to 250 nm to obtain the high-precision nano solder paste.

[0026] By adopting the above technical solution, the preparation method of the present application is simple to operate and has high preparation efficiency. By gradually adding raw materials, it is possible to ensure that all components are evenly dispersed, improve the performance of the flux, and also improve the expansion rate, wettability and stability of the solder paste, making the solder paste more suitable for the needs of precision electronic packaging.

[0027] In summary, the present invention includes at least one of the following beneficial technical effects: 1. This application adopts specific raw materials and proportions to produce high-precision nano solder paste with good storage stability, long service life, high expansion rate and good wetting performance.

[0028] 2. The present application adds glucomannan, which can improve the stability of high-precision nano solder paste and reduce the stratification phenomenon. The present application also adds polyethylene glycol-modified aliphatic epoxy resin, which can increase the expansion rate of solder paste, improve wettability, prevent solder powder from agglomerating, and improve the storage stability of solder paste.

[0029] 3. The preparation method of the present application is simple to operate and has high preparation efficiency. By gradually adding raw materials, it can ensure that all ingredients are evenly dispersed, thereby improving the expansion rate, wettability and stability of the solder paste. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments.

[0031] The present application designs a high-precision nano solder paste, comprising solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin, wherein the weight ratio of the solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin is 85-95:10-15:1-3:1-3; The soldering flux comprises, by mass percentage, 6.3% to 10% of active agent, 0.25% to 1.5% of surfactant, 4% to 10% of thixotropic agent, 1% to 5% of antioxidant, 1% to 3% of corrosion inhibitor, 1% to 5% of film former, and the balance is solvent.

[0032] The high-precision nano solder paste of the present application is prepared by the following method, including the following steps: S1, stirring and mixing the active agent and the solvent to prepare a premixed solution; S2, adding the surfactant, thixotropic agent, antioxidant, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, mixing and stirring the solder powder, the soldering flux, the glucomannan and the polyethylene glycol-modified aliphatic epoxy resin, and grinding them to an average particle size of 100 to 250 nm to obtain the high-precision nano solder paste.

[0033] The present application designs a technical solution to address the problems that the existing high-precision nano solder paste may degrade in performance during storage, affecting its service life and having insufficient expansion rate.

[0034] The raw materials used in this application are as follows: Glucomannan: CAS: 11078-31-2.

[0035] Maleic acid: CAS: 110-16-7.

[0036] p-Toluenesulfonic acid: CAS: 104-15-4.

[0037] Dibromo-butene-diol: CAS: 3234-02-4.

[0038] Cyclohexylamine hydrobromide: CAS: 26227-54-3.

[0039] Hydroxyethyl cellulose: CAS: 9004-62-0.

[0040] Hydrogenated castor oil: CAS: 61788-85-0.

[0041] Mercaptobenzothiazole: CAS: 149-30-4.

[0042] Triphenyl phosphite: CAS: 101-02-0.

[0043] Benzotriazole: CAS: 95-14-7.

[0044] Triethanolamine: CAS: 102-71-6.

[0045] Polyvinyl alcohol: CAS: 9002-89-5.

[0046] Methyl hydrogenated rosinate: CAS: 8050-15-5.

[0047] Isopropyl alcohol: CAS: 67-63-0. Specific embodiments

[0048] Examples 1 to 3 Example 1 This embodiment provides a high-precision nano solder paste, including solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin, wherein the weight ratio of the solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin is 85:10:1:1; The flux is composed of raw materials in percentage by mass: 6.3% activator, 0.25% surfactant, 10% thixotropic agent, 1% antioxidant, 1% corrosion inhibitor, 5% film former, and the balance is solvent; Wherein, the solder powder is SAC 305 alloy powder; The polyethylene glycol-modified aliphatic epoxy resin is prepared by polyethylene glycol and aliphatic epoxy resin, wherein the weight ratio of polyethylene glycol to aliphatic epoxy resin is 1:4; the molecular weight of the aliphatic epoxy resin is 8000, and the epoxy equivalent is 200 g / Eq; The active agent is p-toluenesulfonic acid; the surfactant is dibromo-butylene-diol; the thixotropic agent is hydroxyethyl cellulose; the antioxidant is mercaptobenzothiazole; the corrosion inhibitor is benzotriazole; the film-forming agent is polyvinyl alcohol; and the solvent is isopropyl alcohol.

[0049] The preparation method comprises the following steps: S1, stirring and mixing the active agent and the solvent to prepare a premixed solution; S2, adding a surfactant, a thixotropic agent, an antioxidant, a film-forming agent, and a corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, and preparing a soldering flux; S3. The solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin are mixed and stirred, and ground to an average particle size of 100 nm to obtain a high-precision nano solder paste.

[0050] Example 2 This embodiment provides a high-precision nano solder paste, including solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin, wherein the weight ratio of the solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin is 90:12.5:2:2; The flux is composed of raw materials in percentage by mass: 8.2% of active agent, 0.9% of surfactant, 7% of thixotropic agent, 3% of antioxidant, 2% of corrosion inhibitor, 3% of film former, and the balance of solvent; Wherein, the solder powder is SAC 305 alloy powder; The polyethylene glycol-modified aliphatic epoxy resin is prepared by polyethylene glycol and aliphatic epoxy resin, wherein the weight ratio of polyethylene glycol to aliphatic epoxy resin is 1:4; the molecular weight of the aliphatic epoxy resin is 8000, and the epoxy equivalent is 200 g / Eq; The active agent is p-toluenesulfonic acid; the surfactant is dibromo-butylene-diol; the thixotropic agent is hydroxyethyl cellulose; the antioxidant is mercaptobenzothiazole; the corrosion inhibitor is benzotriazole; the film-forming agent is polyvinyl alcohol; and the solvent is isopropyl alcohol.

[0051] The preparation method comprises the following steps: S1, stirring and mixing the active agent and the solvent to prepare a premixed solution; S2, adding a surfactant, a thixotropic agent, an antioxidant, a film-forming agent, and a corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, and preparing a soldering flux; S3. Solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin are mixed and stirred, and ground to an average particle size of 170 nm to obtain a high-precision nano solder paste.

[0052] Example 3 This embodiment provides a high-precision nano solder paste, including solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin, wherein the weight ratio of the solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin is 95:15:3:3; The flux is composed of raw materials in percentage by mass: 10% activator, 1.5% surfactant, 4% thixotropic agent, 5% antioxidant, 3% corrosion inhibitor, 1% film former, and the balance is solvent; Wherein, the solder powder is SAC 305 alloy powder; The polyethylene glycol-modified aliphatic epoxy resin is prepared by polyethylene glycol and aliphatic epoxy resin, wherein the weight ratio of polyethylene glycol to aliphatic epoxy resin is 1:4; the molecular weight of the aliphatic epoxy resin is 8000, and the epoxy equivalent is 200 g / Eq; The active agent is p-toluenesulfonic acid; the surfactant is dibromo-butylene-diol; the thixotropic agent is hydroxyethyl cellulose; the antioxidant is mercaptobenzothiazole; the corrosion inhibitor is benzotriazole; the film-forming agent is polyvinyl alcohol; and the solvent is isopropyl alcohol.

[0053] The preparation method comprises the following steps: S1, stirring and mixing the active agent and the solvent to prepare a premixed solution; S2, adding a surfactant, a thixotropic agent, an antioxidant, a film-forming agent, and a corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, and preparing a soldering flux; S3. Solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin are mixed and stirred, and ground to an average particle size of 250 nm to obtain a high-precision nano solder paste.

[0054] Comparative Examples 1 to 4 Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that glucomannan and polyethylene glycol-modified aliphatic epoxy resin are not added in Comparative Example 1.

[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that no glucomannan is added in Comparative Example 2.

[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that the polyethylene glycol-modified aliphatic epoxy resin is not added in Comparative Example 3.

[0057] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that the active agent and the solvent are not premixed in Comparative Example 4, and the specific preparation method is as follows: S1, stirring and mixing the active agent, the surfactant, the thixotropic agent, the antioxidant, the film-forming agent, the corrosion inhibitor and the solvent to prepare the soldering flux; S2. Solder powder, flux, glucomannan and polyethylene glycol-modified aliphatic epoxy resin are mixed and stirred, and ground to an average particle size of 170 nm to obtain a high-precision nano solder paste.

[0058] Experimental testing Test items and test methods Storage stability: The prepared high-precision nano solder paste was sealed and stored at 10°C for 6 months to observe whether there was any stratification phenomenon of oil separation; Expansion rate: Test the expansion rate of solder paste according to JIS Z3284; Wetting performance: The wetting performance of solder paste is evaluated according to the solder paste wettability evaluation standard in SJ / T 11186-2019 "General Specification for Solder Paste".

[0059] The high-precision nano solder pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for storage stability, expansion rate, and wetting performance. The test results are shown in Table 1.

[0060] Table 1 Storage stability Expansion rate / % Wetting properties Example 1 No stratification 86.6 Level 1 Example 2 No stratification 87.5 Level 1 Example 3 No stratification 87.0 Level 1 Comparative Example 1 Layered 78.7 Level 2 Comparative Example 2 Layered 79.9 Level 1 Comparative Example 3 Layered 79.1 Level 2 Comparative Example 4 Layered 80.3 Level 1 From the test results in Table 1, it can be seen that the high-precision nano solder pastes prepared in Examples 1 to 3 have good storage stability, no stratification, long service life, high expansion rate, and good wetting performance.

[0061] Comparative Example 1 did not add glucomannan and polyethylene glycol-modified aliphatic epoxy resin, Comparative Example 2 did not add glucomannan, and Comparative Example 3 did not add polyethylene glycol-modified aliphatic epoxy resin. The storage stability of the high-precision nano solder pastes prepared in Comparative Examples 1 to 3 decreased, stratification occurred, and the expansion rate and wetting properties also decreased significantly.

[0062] In Comparative Example 4, the raw materials of the flux were mixed and stirred together without being added sequentially, and the storage stability of the obtained high-precision nano solder paste deteriorated and the expansion rate decreased.

[0063] Embodiments 4 to 13 Example 4 The difference between Example 4 and Example 2 is that in Example 4, the weight ratio of the polyethylene glycol-modified aliphatic epoxy resin to the aliphatic epoxy resin is 1:3.

[0064] Example 5 The difference between Example 5 and Example 2 is that in Example 5, the weight ratio of the polyethylene glycol-modified aliphatic epoxy resin to the aliphatic epoxy resin is 1:5.

[0065] Example 6 The difference between Example 6 and Example 2 is that in Example 6, the molecular weight of the aliphatic epoxy resin is 600, and the epoxy equivalent is 100 g / Eq.

[0066] Example 7 The difference between Example 7 and Example 2 is that in Example 7, the molecular weight of the aliphatic epoxy resin is 1000, and the epoxy equivalent is 300 g / Eq.

[0067] Example 8 The difference between Example 8 and Example 2 is that in Example 8, the active agent is maleic acid.

[0068] Example 9 The difference between Example 9 and Example 2 is that in Example 9, the surfactant is cyclohexylamine hydrobromide.

[0069] Example 10 The difference between Example 10 and Example 2 is that in Example 10, the thixotropic agent is hydrogenated castor oil.

[0070] Embodiment 11 The difference between Example 11 and Example 2 is that in Example 11, the antioxidant is triphenyl phosphite.

[0071] Example 12 The difference between Example 12 and Example 2 is that in Example 12, the corrosion inhibitor is triethanolamine.

[0072] Example 13 The difference between Example 13 and Example 2 is that in Example 13, the film-forming agent is methyl hydrogenated rosin.

[0073] The high-precision nano solder paste prepared in Examples 4 to 13 was tested for storage stability, expansion rate and wetting performance. The test results are shown in Table 2.

[0074] Table 2 Storage stability Expansion rate / % Wetting properties Example 4 No stratification 87.3 Level 1 Example 5 No stratification 87.2 Level 1 Example 6 No stratification 87.4 Level 1 Example 7 No stratification 87.2 Level 1 Example 8 No stratification 87.5 Level 1 Example 9 No stratification 87.3 Level 1 Example 10 No stratification 87.5 Level 1 Embodiment 11 No stratification 87.6 Level 1 Example 12 No stratification 87.3 Level 1 Example 13 No stratification 87.7 Level 1 From the test results in Table 2, it can be seen that the difference between Example 4 and Example 5 and Example 2 is that in the polyethylene glycol-modified aliphatic epoxy resin, the weight ratio of polyethylene glycol to aliphatic epoxy resin is different, and the expansion rate of the obtained high-precision nano solder paste is not as good as that of Example 2.

[0075] The difference between Example 6 and Example 7 and Example 2 is that the molecular weight and epoxy equivalent of the aliphatic epoxy resin are different. Among them, the expansion rate of the high-precision nano solder paste prepared in Example 2 is the best.

[0076] The storage stability, expansion rate and wetting performance of the high-precision nano solder pastes prepared in Examples 8 to 13 are similar to those in Example 2.

[0077] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high-precision nano solder paste, characterized in that: The invention comprises solder powder, flux, glucomannan and polyethylene glycol modified aliphatic epoxy resin, wherein the weight ratio of the solder powder, flux, glucomannan and polyethylene glycol modified aliphatic epoxy resin is 85-95:10-15:1-3:1-3; The soldering flux comprises, by mass percentage, 6.3% to 10% of active agent, 0.25% to 1.5% of surfactant, 4% to 10% of thixotropic agent, 1% to 5% of antioxidant, 1% to 3% of corrosion inhibitor, 1% to 5% of film former, and the balance is solvent.

2. The high-precision nano solder paste according to claim 1, characterized in that: The polyethylene glycol-modified aliphatic epoxy resin is prepared by comprising polyethylene glycol and aliphatic epoxy resin, and the weight ratio of the polyethylene glycol to the aliphatic epoxy resin is 1:3-5.

3. The high-precision nano solder paste according to claim 2, characterized in that: The molecular weight of the aliphatic epoxy resin is 600-1000, and the epoxy equivalent of the aliphatic epoxy resin is 100-300 g / Eq.

4. The high-precision nano solder paste according to claim 1, characterized in that: The active agent is selected from at least one of maleic acid, p-toluenesulfonic acid and sulfosalicylic acid.

5. The high-precision nano solder paste according to claim 1, characterized in that: The surfactant is selected from at least one of dibromo-butene-diol, cyclohexylamine hydrobromide and 3-bromo-1-propanol.

6. The high-precision nano solder paste according to claim 1, characterized in that: The thixotropic agent is selected from at least one of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydrogenated castor oil.

7. The high-precision nano solder paste according to claim 1, characterized in that: The antioxidant is selected from at least one of N,N'-di-sec-butyl-p-phenylenediamine, mercaptobenzothiazole and triphenyl phosphite.

8. The high-precision nano solder paste according to claim 1, characterized in that: The corrosion inhibitor is selected from at least one of benzotriazole, 2-methylbenzimidazole and triethanolamine; The film-forming agent is selected from at least one of polyvinyl alcohol, polyvinyl pyrrolidone and methyl hydrogenated rosin.

9. The high-precision nano solder paste according to claim 1, characterized in that: The solvent is selected from at least one of ethanol, isopropanol and propylene glycol.

10. A method for preparing the high-precision nano solder paste according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, stirring and mixing the active agent and the solvent to prepare a premixed solution; S2, adding the surfactant, thixotropic agent, antioxidant, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, mixing and stirring the solder powder, the soldering flux, the glucomannan and the polyethylene glycol-modified aliphatic epoxy resin, and grinding them to an average particle size of 100-250 nm to obtain the high-precision nano solder paste.

Citation Information

Patent Citations

  • Lithium battery negative electrode mixture, negative electrode and lithium ion battery

    CN106920968A

  • Soldering paste capable of resisting high-temperature post-welding residues and preparation process of soldering paste

    CN117444471A

  • High-temperature-resistant hot melt adhesive for PET bottle labeling and preparation process of high-temperature-resistant hot melt adhesive

    CN117447951A

  • High-precision nano soldering paste and preparation method thereof

    CN117484007A

  • Soldering paste with stable performance and preparation method thereof

    CN118478135A